Intraspecific Variation in Sensitivity of UV-B Radiation in Rice - Barnes, Paul W.; Maggard, Sharon; Holman, Steven R.; Vergara, Benito S. (Wiley, 1993)
Twenty‐two cultivars of rice (Oryza sativa L.) from diverse origins were grown under greenhouse conditions and exposed to ultraviolet‐B radiation (UV‐B; 280‐320 nm) simulating a 5% reduction in stratospheric ozone in spring for the Philippines (14° N lat.) to evaluate growth and morphological responses to UV‐B. In comparison to controls that received no UV‐B, plants exposed to UV‐B exhibited significantly reduced dry matter production (total plant and shoot), shoot height, leaf blade length and total leaf area, increased number of tillers, and greater weight fractions in leaf blades and roots. For most cultivars, the relative effects of UV‐B on shoot morphology were greater than the effects on biomass production. The direction of the UV‐B effects were generally similar for all cultivars, however, there were significant differences among cultivars in the magnitude of the UV‐Binduced changes. Upland cultivars (IRAT104 and OS4) and two lowland cultivars commonly planted in the USA (Star Bonnet and Lemont) were found to be least affected by the UV‐B, whereas modern, high yielding, lowland cultivars developed in the Philippines (IR52, IR35546‐17‐33, and IR58) were found to be among the most sensitive to UV‐B. Our results indicate that in rice, as in other grasses, shoot morphology may be more responsive to solar UV‐B change than plant productivity. Intraspecific variation in morphological responses to UVB could contribute to differences among cultivars in susceptibility to UV‐B‐induced changes in competitive balance between rice and associated weeds of the rice agroecosystem.